COVID-19 test before Tokyo2020 Paralympic Games: An implemented protocol to protect Paralympic Athletes - Muti, G. E.; Muti-Schuenemann, G.; Pimpinelli, F.; Spataro, A.; Fiore, A.; Ciasullo, F.; Olivieri, D.; Rigoni, M.; Delbue, S.; Pariani, E.; Muzi, F.; Donzelli, S.; et al. (Frontiers in Sports and Active Living, 2022)
Objectives: The COVID-19 pandemic represents a difficult challenge for the whole of humanity. Sports, in which contact between athletes is essential, became impossible to practice without the risk of viral spread. Athletes of the national teams are a particular subgroup of the population for whom there is an important need for protection and the implementation of targeted preventive measures. The present report describes the protocol that was developed to answer the urgent protection need for athletes during COVID-19 pandemic. The protocol aimed at demonstrating the feasibility of a rigid prevention intervention to prevent outbreaks and infections in terms of COVID-19 as well as in other potential future pandemics from pathogens with similar path of transmission.